Figure 4 from: Juswara L, Schuiteman A, Droissart V (2016) Four new orchid species from the Lengguru fold belt, West Papua, Indonesia. PhytoKeys 61: 47-59. https://doi.org/10.3897/phytokeys.61.7590 - Juswara, Lina; Schuiteman, Andre; Droissart, Vincent (Zenodo, 2016)
Figure 4 - Photographs of living type specimens and habitats. Dendrobium taeniocaule: A habitat and habit B plant C flower and part of pseudobulb D flower, front view E flower, side view. Taeniophyllum pyriforme: F habitat and habit G plant and inflorescence H inflorescence and flowers close-up. Photos: Vincent Droissart.